2018
DOI: 10.5194/acp-18-7251-2018
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the condensation–collision size gap: a direct numerical simulation of continuous droplet growth in turbulent clouds

Abstract: Abstract. In most previous direct numerical simulation (DNS) studies on droplet growth in turbulence, condensational growth and collisional growth were treated separately. Studies in recent decades have postulated that small-scale turbulence may accelerate droplet collisions when droplets are still small when condensational growth is effective. This implies that both processes should be considered simultaneously to unveil the full history of droplet growth and rain formation. This paper introduces the first di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
(42 reference statements)
2
28
0
Order By: Relevance
“…Contrary to the classical treatment of condensational growth, our findings demonstrate that the supersaturation fluctuation-induced condensational growth facilitates the collisional growth by broadening the width of the droplet size distribution. Chen et al (2018b) compared droplet size distributions for differentε when both condensation and collision were included. They attributed the condensation-induced collision to the fact that "condensational growth narrows the droplet size distribution (DSD) and provides a great number of similar-sized droplets" (Chen et al 2018b), which is inconsistent with our finding that condensational growth produces wider distributions with increasing Re λ and therefore facilitates the collisional growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the classical treatment of condensational growth, our findings demonstrate that the supersaturation fluctuation-induced condensational growth facilitates the collisional growth by broadening the width of the droplet size distribution. Chen et al (2018b) compared droplet size distributions for differentε when both condensation and collision were included. They attributed the condensation-induced collision to the fact that "condensational growth narrows the droplet size distribution (DSD) and provides a great number of similar-sized droplets" (Chen et al 2018b), which is inconsistent with our finding that condensational growth produces wider distributions with increasing Re λ and therefore facilitates the collisional growth.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2018b) compared droplet size distributions for differentε when both condensation and collision were included. They attributed the condensation-induced collision to the fact that "condensational growth narrows the droplet size distribution (DSD) and provides a great number of similar-sized droplets" (Chen et al 2018b), which is inconsistent with our finding that condensational growth produces wider distributions with increasing Re λ and therefore facilitates the collisional growth. However, we emphasize that there are two crucial differences compared to our present model.…”
Section: Discussionmentioning
confidence: 99%
“…These structures distinguish fully developed turbulence from purely random flow fields, and must play an important role in many aspects of turbulent transport. The most important of these-because it remains central to our understanding of phenomena as diverse as the formation of planets in circumstellar disks [17] or the initiation of rain in warm clouds [18,19]is the growth of macroscopic aggregates, due to collisions and coalescences, from nuclei-particles (dust or aerosols) suspended in a turbulent flow. The role of the underlying turbulent carrier flow is critical: Estimates of, e.g., the rate of growth of these aggregates in the absence of such flows do not agree with that seen in nature [20].…”
mentioning
confidence: 99%
“…The ultimate goal is to provide a high-resolution benchmarking to the cloud physics community to better understand aerosol-cloud-precipitation interaction, in the hope of 50 improving the representation of clouds and precipitation in numerical weather and climate prediction. Chen et al (2018b) found that the evolution of droplet size distribution (DSD) has very different response mechanisms to turbulence depending on whether droplets grow by condensation-only, collision-only, or condensation-collision simultaneously ( Fig. 1 in their paper).…”
mentioning
confidence: 99%
“…Many past DNS studies focusing on either the condensation-only process or the 55 collision-only process might, therefore, yield biased results. This paper presents a sequel to the study of Chen et al (2018b) by addressing several caveats mentioned in their paper. Firstly, Chen et al (2018b) treated only pure water droplets as is 2 https://doi.no significant change is found in the effective droplet radius, and the relative dispersion is only slightly reduced (Fig.…”
mentioning
confidence: 99%